Catalyst for efficient PET degradation and preparation method thereof
By preparing a catalyst composed of a variety of metal oxides and other additives, the existing optical catalysts have the lack of PET degradation efficiency, stability and reusing use, and achieve an efficient and stable PET degradation effect.
Patent Information
- Application Number
- CN202411124388.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-16
- Publication Date
- 2025-01-21
AI Technical Summary
Existing photocatalysts have shortcomings in PET degradation efficiency, catalytic stability and reusability, making it difficult to effectively solve the environmental pollution problems in PET waste treatment.
Using catalysts consisting of titanium dioxide, zinc oxide, cobalt oxide, nano -titanium dioxide, silicane coupling agent, and rushing agent, it is prepared through steps such as specific mixing, grinding, burning, restore treatment, etc. to form a high ratio of high ratio and excellent photocatalytic activity catalyst.
The degradation efficiency and stability of the catalyst are significantly improved, and PET can be efficiently degraded in a short time, and the catalyst has good reusability and structural stability.
Smart Images

Figure CN119327464A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalysts, and in particular relates to a catalyst for efficient PET degradation and a preparation method thereof. Background Art
[0002] With the widespread use of plastic products, polyethylene terephthalate (PET), as a major plastic material, is widely used in food and beverage packaging, fiber manufacturing and other industrial fields. However, the widespread use of PET has also brought serious environmental pollution problems because it is difficult to degrade in the natural environment. Traditional PET waste treatment methods mainly include landfill and incineration, but these methods are not only inefficient, but also produce secondary pollution. Therefore, it is of great practical significance to develop an efficient and environmentally friendly PET degradation method.
[0003] Photocatalytic degradation is a promising method for PET degradation, which uses active oxygen species produced by photocatalysts under light conditions to decompose PET into small molecules and ultimately achieve degradation. However, current photocatalysts still have many problems in terms of degradation efficiency, catalytic stability and reusability.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art, provide a catalyst for efficient PET degradation and a preparation method thereof, and solve the problems raised in the above background technology.
[0006] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is:
[0007] A catalyst for efficient PET degradation and a preparation method thereof, comprising a mixture of the following raw materials in percentage: 25-50% titanium dioxide, 15-40% zinc oxide, 10-23% cobalt oxide, 2-14% nano titanium dioxide, 2-11% silane coupling agent and 1-76% reducing agent.
[0008] Optionally, the silane coupling agent is γ-aminopropyltriethoxysilane.
[0009] Optionally, the reducing agent is hydrogen, and nitrogen is used as an inert gas protection during the reduction process.
[0010] Optionally, titanium dioxide is a white powder with a particle size of 50-100 nanometers, zinc oxide is a white crystalline powder with a particle size of 30-50 nanometers, cobalt oxide is a dark red powder with a particle size of 1-5 microns, and nano titanium dioxide is white nanoparticles with a particle size of 10-30 nanometers.
[0011] A method for preparing a catalyst for efficient PET degradation comprises the following steps:
[0012] Step (1): titanium dioxide, zinc oxide and cobalt oxide are mixed in proportion and ground evenly to obtain a mixture ① after the mixture is ground evenly;
[0013] Step (2): adding nano titanium dioxide to the obtained mixture ①, and continuing grinding to obtain a mixture ②;
[0014] Step (3): adding ethanol to the obtained mixture ② and stirring the mixture until a slurry is formed after the mixture is stirred evenly;
[0015] Step (4): calcining the slurry, and after the ethanol is completely volatilized during the calcination process, a mixture ③ can be obtained;
[0016] Step (5): adding a stabilizer silane coupling agent to the mixture ③ and performing secondary calcination to obtain the product ①;
[0017] Step (6): adding a reducing agent to the product ① and performing a reduction treatment to obtain the product ②;
[0018] Step (7): cooling the product ② and suspending the cooled product ② in deionized water and treating it with ultrasound for 30 minutes to obtain product ③;
[0019] Step (8): freeze-drying the product ③ to remove water to obtain product ④;
[0020] Step (9): Screen the product ④ to obtain a catalyst.
[0021] Optionally, the mass ratio of ethanol to mixture ② is 1:1.5, and the mixing and grinding time in step (1) is 30-40 minutes. By controlling the mass ratio of ethanol to mixture ②, it can be ensured that the formed slurry has good fluidity and uniformity, which helps to form a catalyst with stable structure during the calcination process. The mixing and grinding time of 30-40 minutes can make the components fully contact and evenly dispersed to form a homogeneous mixture, providing a good foundation for subsequent calcination and reduction treatment.
[0022] Optionally, the calcination temperature in step (4) is 550°C-600°C and the time is 2-3 hours. The temperature and time of the calcination have an important influence on the performance and structure of the catalyst. By calcining at 550-600°C for 2-3 hours, the organic components in the mixture can be fully decomposed to form a stable catalyst structure while retaining the chemical properties of the active components.
[0023] Optionally, the temperature of the secondary calcination treatment in step (5) is 260°C-400°C, and the time is 1-3 hours. The secondary calcination treatment can further improve the stability and activity of the catalyst. By performing the secondary calcination treatment at 260-400°C for 1-3 hours, the added stabilizer can be fully reacted to form a stable chemical bond, thereby improving the mechanical strength and chemical stability of the catalyst.
[0024] Optionally, the temperature of the reduction treatment in step (6) is 300°C-600°C, and the time is 1-2 hours. By performing the reduction treatment at 300-600°C for 1-2 hours, the oxide can be effectively reduced, and the structure and performance of the catalyst can be improved, so that it exhibits higher activity and stability in the process of degrading PET. The freeze-drying temperature of -10°C to -50°C can effectively prevent the catalyst from undergoing structural changes or performance degradation during the drying process. The drying time of 6-12 hours can ensure that the moisture in the catalyst is completely removed to obtain a final product with stable performance.
[0025] Optionally, the freeze-drying temperature in step (8) is -10°C to 50°C, and the time is 6 to 12 hours.
[0026] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art. Of course, any product implementing the present invention does not necessarily need to achieve all the advantages described below at the same time:
[0027] The titanium dioxide of the present invention provides a high specific surface area and excellent photocatalytic activity, which significantly improves the degradation efficiency of the catalyst; secondly, the nano titanium dioxide further improves the photocatalytic performance of the catalyst by increasing the specific surface area and active sites. The synergistic effect of the two materials enables the catalyst to show higher performance in the process of degrading PET and can achieve efficient degradation in a shorter time. In addition, the particle size distribution of the nano titanium dioxide is uniform, which helps to improve the dispersibility and stability of the catalyst, prevent agglomeration during use, and thus extend the service life of the catalyst.
[0028] The specific implementation modes of the present invention are further described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The drawings described below are only some embodiments. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0030] In the figure:
[0031] Figure 1 is the SEM image of Example 1;
[0032] Figure 2is the SEM image of Example 2;
[0033] Figure 3 This is the SEM image of Example 3.
[0034] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but are intended to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION
[0035] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0036] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0037] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0038] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0039] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0040] The embodiment of the invention discloses a catalyst for efficient PET degradation, which is prepared by mixing the following raw materials in percentage: 25-50% titanium dioxide, 15-40% zinc oxide, 10-23% cobalt oxide, 2-14% nano titanium dioxide, 2-11% silane coupling agent and 1-76% reducing agent.
[0041] In some embodiments of the present invention, the silane coupling agent is γ-aminopropyltriethoxysilane.
[0042] In some embodiments of the present invention, the reducing agent is hydrogen, and nitrogen is used as an inert gas protection during the reduction process.
[0043] In some embodiments of the present invention, titanium dioxide is in the form of a white powder with a particle size of 50-100 nanometers, zinc oxide is in the form of a white crystalline powder with a particle size of 30-50 nanometers, cobalt oxide is in the form of a dark red powder with a particle size of 1-5 micrometers, and nano titanium dioxide is in the form of white nanoparticles with a particle size of 10-30 nanometers.
[0044] A method for preparing a catalyst for efficient PET degradation comprises the following steps:
[0045] Step (1): titanium dioxide, zinc oxide and cobalt oxide are mixed in proportion and ground evenly to obtain a mixture ① after the mixture is ground evenly;
[0046] Step (2): adding nano titanium dioxide to the obtained mixture ①, and continuing grinding to obtain a mixture ②;
[0047] Step (3): adding ethanol to the obtained mixture ② and stirring the mixture until a slurry is formed after the mixture is stirred evenly;
[0048] Step (4): calcining the slurry, and after the ethanol is completely volatilized during the calcination process, a mixture ③ can be obtained;
[0049] Step (5): adding a stabilizer silane coupling agent to the mixture ③ and performing secondary calcination to obtain the product ①;
[0050] Step (6): adding a reducing agent to the product ① and performing a reduction treatment to obtain the product ②;
[0051] Step (7): cooling the product ② and suspending the cooled product ② in deionized water and treating it with ultrasound for 30 minutes to obtain product ③;
[0052] Step (8): freeze-drying the product ③ to remove water to obtain product ④;
[0053] Step (9): Screen the product ④ to obtain a catalyst.
[0054] In some embodiments of the present invention, the mass ratio of ethanol to mixture ② is 1:1.5, and the time of mixing and grinding in step (1) is 30-40min. By controlling the mass ratio of ethanol to mixture ②, it can be ensured that the formed slurry has good fluidity and uniformity, which helps to form a catalyst with stable structure during the calcination process. The mixing and grinding time of 30-40 minutes enables each component to fully contact and evenly disperse to form a homogeneous mixture, providing a good basis for subsequent calcination and reduction treatment.
[0055] In some embodiments of the present invention, the calcination temperature in step (4) is 550°C-600°C and the time is 2-3 hours. The temperature and time of the calcination have an important influence on the performance and structure of the catalyst. By calcining at 550-600°C for 2-3 hours, the organic components in the mixture can be fully decomposed to form a stable catalyst structure while retaining the chemical properties of the active components.
[0056] In some embodiments of the present invention, the temperature of the secondary calcination treatment in step (5) is 260°C-400°C, and the time is 1-3 hours. The secondary calcination treatment can further improve the stability and activity of the catalyst. By performing the secondary calcination treatment at 260-400°C for 1-3 hours, the added stabilizer can be fully reacted to form a stable chemical bond, thereby improving the mechanical strength and chemical stability of the catalyst.
[0057] In some embodiments of the present invention, the temperature of the reduction treatment in step (6) is 300°C-600°C, and the time is 1-2 hours. By performing the reduction treatment at 300-600°C for 1-2 hours, the oxide can be effectively reduced, the structure and performance of the catalyst can be improved, and it can show higher activity and stability in the process of degrading PET. The freeze-drying temperature of -10°C to -50°C can effectively prevent the catalyst from undergoing structural changes or performance degradation during the drying process. The drying time of 6-12 hours can ensure that the moisture in the catalyst is completely removed to obtain a final product with stable performance.
[0058] In some embodiments of the present invention, the freeze-drying temperature in step (8) is -10°C to 50°C, and the time is 6 to 12 hours.
[0059] The present invention will now be further described in detail with reference to embodiments.
[0060] It should be noted that all raw materials in the examples of the present invention were obtained through commercial sources.
[0061] Example 1: In this example, a method for preparing a catalyst for efficient PET degradation is provided, comprising the following steps:
[0062] Step (1): 30% titanium dioxide, 20% zinc oxide and 15% cobalt oxide are mixed in proportion and ground evenly for 30 minutes to obtain a mixture ①; Step (2): 10% nano titanium dioxide is added to the mixture ① and the grinding is continued for 30 minutes to obtain a mixture ②; Step (3): ethanol is added to the mixture ②, the mass ratio of ethanol to the mixture ② is 1:1.5, and the mixture is stirred evenly to form a slurry; Step (4): The slurry is calcined at 550° C. for 2 hours, and the ethanol is volatilized to obtain a mixture ③; Step (5): 10% silane coupling agent is added to the mixture ③, and secondary calcination is carried out at 260°C for 2 hours to obtain product ①; step (6): 15% reducing agent is added to the product ①, and reduction treatment is carried out at 300°C for 1.5 hours to obtain product ②; step (7): product ② is cooled, suspended in deionized water and treated with ultrasound for 30 minutes to obtain product ③; step (8): product ③ is freeze-dried at -20°C for 8 hours to obtain product ④; step (9): product ④ is sieved to obtain the final catalyst.
[0063] See also Figure 1 As shown, a degradation experiment was carried out using 0.1g of catalyst in 250ml of aqueous solution containing 1g of PET flakes. The experimental results are as follows:
[0064] Under ultraviolet light, the reaction time is 3 hours, and PET is completely degraded to produce terephthalic acid and ethylene glycol. GC-MS analysis confirmed that the purity of the degradation product is as high as 98.5%. After the catalyst is recycled for 5 times, the degradation efficiency remains above 90%, showing good reusability. After each cycle, the structure and morphology of the catalyst do not change significantly. After each cycle, XRD analysis shows that the crystal phase of the catalyst does not change significantly, and SEM images show that the particle morphology remains stable.
[0065] Example 2: In this example, a method for preparing a catalyst for efficient PET degradation is provided, comprising the following steps:
[0066] Step (1): 40% titanium dioxide, 25% zinc oxide and 13% cobalt oxide are mixed in proportion and ground evenly for 35 minutes to obtain a mixture ①; Step (2): 8% nano titanium dioxide is added to the mixture ① and the grinding is continued for 35 minutes to obtain a mixture ②; Step (3): ethanol is added to the mixture ②, the mass ratio of ethanol to the mixture ② is 1:1.5, and the mixture is stirred evenly to form a slurry; Step (4): The slurry is calcined at 570° C. for 3 hours, and the ethanol is volatilized to obtain a mixture ③; Step (5): Add 5% silane coupling agent to mixture ③, and perform secondary calcination at 300°C for 2 hours to obtain product ①; step (6): add 9% reducing agent to product ①, and perform reduction treatment at 350°C for 2 hours to obtain product ②; step (7): cool product ②, suspend it in deionized water and use ultrasonic treatment for 30 minutes to obtain product ③; step (8): freeze-dry product ③ at -30°C for 10 hours to obtain product ④; step (9): sieve product ④ to obtain the final catalyst.
[0067] See also Figure 2 As shown, a degradation experiment was carried out using 0.1g of catalyst in 250ml of aqueous solution containing 1g of PET flakes. The experimental results are as follows:
[0068] Under ultraviolet light (λ=365nm), the reaction time was 2.5 hours, the PET degradation rate reached 88%, and the main degradation products were terephthalic acid (PTA) and ethylene glycol (EG). GC-MS analysis confirmed that the purity of the degradation product PTA was 98.5%, and the purity of EG was 98%.
[0069] Embodiment 3: In this embodiment, a method for preparing a catalyst for efficient PET degradation is provided, comprising the following steps:
[0070] Step (1): 45% titanium dioxide, 30% zinc oxide and 10% cobalt oxide are mixed in proportion and ground evenly for 40 minutes to obtain a mixture ①; Step (2): 5% nano titanium dioxide is added to the mixture ① and the grinding is continued for 40 minutes to obtain a mixture ②; Step (3): ethanol is added to the mixture ②, the mass ratio of ethanol to the mixture ② is 1:1.5, and the mixture is stirred evenly to form a slurry; Step (4): The slurry is calcined at 580° C. for 2.5 hours, and the ethanol is volatilized to obtain a mixture ③; Step (5) : Add 4% silane coupling agent to mixture ③, and calcine it twice at 280℃ for 3 hours to obtain product ①; step (6): add 6% reducing agent to product ①, and reduce it at 400℃ for 1 hour to obtain product ②; step (7): cool product ②, suspend it in deionized water and use ultrasonic treatment for 30 minutes to obtain product ③; step (8): freeze-dry product ③ at -40℃ for 12 hours to obtain product ④; step (9): sieve product ④ to obtain the final catalyst.
[0071] See also Figure 3 As shown, a degradation experiment was carried out using 0.1g of catalyst in 250ml of aqueous solution containing 1g of PET flakes. The experimental results are as follows:
[0072] Under ultraviolet light (λ=365nm), the reaction time is 2 hours, and the PET degradation rate reaches 90%, and the main degradation products are terephthalic acid (PTA) and ethylene glycol (EG). Through GC-MS analysis, it is confirmed that the purity of the degradation product PTA is 99%, and the purity of EG is 98.5%. After the catalyst is recycled for 5 times, the degradation efficiency remains above 87%, and the performance is stable. After each cycle, XRD analysis shows that the crystal phase of the catalyst has no significant change, and SEM images show that the particle morphology remains stable.
[0073] The catalysts in Examples 1-3 of the present application are all white to light yellow powders, with uniform particles and no obvious agglomeration, showing good preparation technology and uniform dispersion. Moreover, the catalysts of the present application have a high specific surface area, which helps to increase active sites, thereby improving their catalytic performance.
[0074] The present invention is not limited to the above-mentioned embodiments. Anyone should be aware that any structural changes made under the enlightenment of the present invention, and any technical solutions that are the same or similar to the present invention, fall within the protection scope of the present invention. The technology, shape, and structural parts not described in detail in the present invention are all well-known technologies.
Claims
1. A catalyst for efficient PET degradation, characterized in that: The invention comprises a mixture of raw materials in the following percentages: 25-50% titanium dioxide, 15-40% zinc oxide, 10-23% cobalt oxide, 2-14% nano titanium dioxide, 2-11% silane coupling agent and 1-76% reducing agent.
2. A catalyst for efficient PET degradation and a preparation method thereof according to claim 1, characterized in that: The silane coupling agent is γ-aminopropyltriethoxysilane.
3. A catalyst for efficient PET degradation and a preparation method thereof according to claim 1, characterized in that: The reducing agent is hydrogen, and nitrogen is used as an inert gas protection during the reduction process.
4. A catalyst for efficient PET degradation and a preparation method thereof according to claim 1, characterized in that: Titanium dioxide is a white powder with a particle size of 50-100 nanometers, zinc oxide is a white crystalline powder with a particle size of 30-50 nanometers, cobalt oxide is a dark red powder with a particle size of 1-5 microns, and nano titanium dioxide is white nanoparticles with a particle size of 10-30 nanometers.
5. A method for preparing the catalyst for efficient PET degradation according to claims 1-4, characterized in that: The following steps are involved: Step (1): titanium dioxide, zinc oxide and cobalt oxide are mixed in proportion and ground evenly to obtain a mixture ① after the mixture is ground evenly; Step (2): adding nano titanium dioxide to the obtained mixture ①, and continuing grinding to obtain a mixture ②; Step (3): adding ethanol to the obtained mixture ② and stirring the mixture until a slurry is formed after the mixture is evenly stirred; Step (4): calcining the slurry, and after the ethanol is completely volatilized during the calcination process, a mixture ③ can be obtained; Step (5): adding a stabilizer silane coupling agent to the mixture ③ and performing secondary calcination to obtain the product ①; Step (6): adding a reducing agent to the product ① and performing a reduction treatment to obtain the product ②; Step (7): cooling the product ② and suspending the cooled product ② in deionized water and treating it with ultrasound for 30 minutes to obtain product ③; Step (8): freeze-drying the product ③ to remove water to obtain product ④; Step (9): Screen the product ④ to obtain a catalyst.
6. The method for preparing a catalyst for efficient PET degradation according to claim 5, characterized in that: The mass ratio of ethanol to mixture ② is 1:1.5, and the mixing and grinding time in step (1) is 30-40 minutes.
7. The method for preparing a catalyst for efficient PET degradation according to claim 5, characterized in that: The calcination temperature in step (4) is 550°C-600°C and the calcination time is 2-3 hours.
8. The method for preparing a catalyst for efficient PET degradation according to claim 5, characterized in that: The temperature of the secondary calcination treatment in step (5) is 260°C-400°C, and the time is 1-3 hours.
9. The method for preparing a catalyst for efficient PET degradation according to claim 5, characterized in that: The temperature of the reduction treatment in step (6) is 300°C-600°C, and the time is 1-2 hours.
10. The method for preparing a catalyst for efficient PET degradation according to claim 5, characterized in that: The freeze-drying temperature in step (8) is -10°C to 50°C, and the time is 6 to 12 hours.